2011
DOI: 10.1063/1.3537809
|View full text |Cite
|
Sign up to set email alerts
|

Bond-specific reaction kinetics during the oxidation of (111) Si: Effect of n-type doping

Abstract: It is known that a higher concentration of free carriers leads to a higher oxide growth rate in the thermal oxidation of silicon. However, the role of electrons and holes in oxidation chemistry is not clear. Here, we report real-time second-harmonic-generation data on the oxidation of H-terminated (111)Si that reveal that high concentrations of electrons increase the chemical reactivity of the outer-layer Si-Si back bonds relative to the Si-H up bonds. However, the thicknesses of the natural oxides of all samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…For carrier concentrations of p = ∼ 10 15 cm −3 as well as 10 16 cm −3 we see that the incubation periods for the back bonds Here the incubation appears to be completely missing and the evolution is a simple exponential rise with a negative time constant, suggesting that the oxidation process is rising to a saturation level. Our ellipsometric data (not shown) show that for both n-and p-type samples oxidation continues until the thickness reaches a certain value, that is independent of carrier type and concentration [20]. These results are consistent with corrosion studies of Si and Ge in aqueous solutions, where the availability of holes which weakens the surface bonds is the rate-limiting step.…”
Section: This Analysis Shows That the Initial Oxidation Of P-typesupporting
confidence: 87%
See 1 more Smart Citation
“…For carrier concentrations of p = ∼ 10 15 cm −3 as well as 10 16 cm −3 we see that the incubation periods for the back bonds Here the incubation appears to be completely missing and the evolution is a simple exponential rise with a negative time constant, suggesting that the oxidation process is rising to a saturation level. Our ellipsometric data (not shown) show that for both n-and p-type samples oxidation continues until the thickness reaches a certain value, that is independent of carrier type and concentration [20]. These results are consistent with corrosion studies of Si and Ge in aqueous solutions, where the availability of holes which weakens the surface bonds is the rate-limiting step.…”
Section: This Analysis Shows That the Initial Oxidation Of P-typesupporting
confidence: 87%
“…[19] In addition, we found that the excess electrons in a heavily n-type sample change oxidation kinetics of the different surface bonds dramatically. [20] Here, we extend these studies to (111) surfaces of p-type Si wafers. We also performed atomic force microscopy (AFM) measurements, which provide additional information via changes in surface morphology.…”
mentioning
confidence: 78%
“…It was demonstrated that the carrier type—instead of dopant type—enhanced the etching rate of n + -Si in the H 2 O 2 q-ALE process. The high concentration of electrons in n + -Si might accelerate oxide growth in H 2 O 2 solutions, which could be explained by the improved relativity of Si-Si back bonds [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47][48] This would lead to important microscopic insights into surface chemical bonding via the associated changes in bond hyperpolarizabilities.…”
Section: Regime Iii: Chemical Modification Of the Surfacementioning
confidence: 99%